واقع استخدام الحاسب الآلي من قبل اعضاءهيئة التدريس بكلية المعلمين بجامعة تبوك واتجاهاتهم نحوه - قحطاني، خالد بن ناصر (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2013)
This study aims at identifying the use of computer and educational technology in teaching among teaching staff at the Male Teachers College in Tabuk University. It attempts to address the use of computers by the teaching staff at the Male Teachers College in Tabuk University, and to measure the faculty teaching staff attitudes about the use of computers in teaching. Two main research instruments were used to gather the data. These instruments were administered on ٧٩ teaching staff from the said University. The study used several statistical methods such as descriptive statistics in terms of mean and standard deviation and inferential statistics such as Kruskal-Wallis and Pearson Correlation. The results of the study show that there is a positive relationship between the use of computers and the attitude towards its use. Most of teaching staff strongly supported the use of computer and educational technology. It was found that the teaching staff attitude was averagely towards the use of computer and technologies in teaching. Based on this, the study recommended a need to adopt pre-service training programs for faculty members at the Male Teachers College in Tabuk University to keep pace with developments in the field of educational technology as well developing staff in their profession. It also recommended that there is a need for employing technicians to assist teaching staff in the computer labs and educational technology during teaching.